Dunggala Digital Hub: Multidisciplinary Synergy in Branding Local Wisdom through English Educational Content for Global Marketing: Pengabdian - Haris Danial; Nonny Basalama; Muhammad Rezky Friesta Payu; Indri Wirahmi Bay (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The community service program entitled Dunggala Digital Hub: Multidisciplinary Synergy in Branding Local Wisdom through English Educational Content for Global Marketing was successfully implemented in Dunggala Village, Tapa District, Bone Bolango Regency for 45 days. The program aimed to improve the quality of education, digital literacy, and the strengthening of the community’s creative economy through technology-based and local wisdom-oriented approaches. The implementation of the program began with field observations and community needs analysis to identify various village problems, such as low digital literacy, the lack of optimal promotion of local potential, and the underutilization of coconut coir waste. Various activities were successfully carried out, including educational programs for school children, disaster mitigation socialization, digital data collection for aid recipients, training in educational content production and village promotion in English, as well as the GALAPEAT program, which focused on processing coconut coir waste into organic planting media (cocopeat). In addition, social activities such as Friday Clean-Up programs, Posyandu services, Qur’an donations, and Dunggala CUP also strengthened community participation and the culture of mutual cooperation. Overall, the program had a positive impact on improving knowledge, skills, digital literacy, and the branding of Dunggala Village as an innovative village based on local wisdom.